Anticipated and unanticipated difficult airway management. Issue 1 (February 2018) - Xu, Zeping; Ma, Wuhua; Hester, Douglas L.; Jiang, Yandong
Abstract : Purpose of review: Management of difficult airway is far from optimal despite of continuous progress in science and technology. The purpose of this review is to summarize the current research in the field and bring readers up to date. Recent findings: New technologies for intubation make providers more confident to handle difficult airways, but there is lack of evidence indicating the reduction in incidence of 'cannot intubate cannot ventilate (CICV)'. Optimization of mask ventilation should reduce the incidence of difficult mask ventilation but it is greatly underappreciated. Even optimization of preoxygenation is not directly associated with any decreased incidence of difficult airway, but it prolongs time of safe apnea oxygenation; therefore, is likely to improve the outcome of the patients if CICV occurs. Summary: Improvement of managing difficult airway relies on optimized mask ventilation, utilization of the appropriate tools for intubation, maximization of the safe apnea oxygenation time, prompt surgical airway in response to severe hypoxia in case effective noninvasive interventions are not achievable. It seems that a simplified and concise algorithm of difficult airway management needs to be established in order to enable providers to easily remember and execute.